Andean N°6 - César Leonardo Munive Carrión (2022)
The commemoration of the first three decades of the Universidad Andina Simón Bolívar, Ecuador Campus, serves as the central theme of the sixth issue of Andina magazine, creating a profound institutional record that intertwines the history and future of higher education in the region. Through the valuable testimony of Enrique Ayala Mora, the origins and consolidation of this academic project are reconstructed, recalling everything from the initial campus agreements and strategic alliances to the complex political and budgetary challenges and institutional evaluations that the university had to navigate over the years to preserve its autonomy and scientific rigor. This chronicle not only pays tribute to the past but also highlights the collective effort of staff, faculty, and workers who, from the most basic tasks of the university’s founding to IT and library support, laid the foundations of a community committed to social development.
Keywords: History; Poetry; Chronicle; Public policy; Culture